Demilitarization and neutralization – the case of the Åland Islands - Brańka, Tomasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
Demilitarization and neutralization are among the specific restrictions that apply to the exercise of territorial sovereignty. Although frequently employed in international practice, no generally accepted definitions are available for either of these concepts. The void has given rise to a host of interpretations, which vary particularly widely in the case of demilitarization. The Åland Islands are a classic example of an area that has been both militarized and neutralized. Owing to its strategic location, it has repeatedly become the focal point of political clashes between European powers over the last two centuries. The Islands were seen as a key to pursuing Baltic Sea policies and balancing the strengths of European powers. The conflicts that swept through the region in the 19th century led to the gradual improvement of methods to demilitarize and subsequently neutralize the archipelago. Its status was ultimately settled in 1921 by an international convention and recognized after the end of World War II. The international legal status granted to the archipelago at that time has persisted to this day and continues to serve as a model of effective demilitarization and neutralization.

Demilitaryzacja i neutralizacja należą do katalogu szczególnych ograniczeń wykonywania zwierzchnictwa terytorialnego. Pomimo, iż są to rozwiązania stosowane w praktyce międzynarodowej stosunkowo często, to brakuje powszechnie uznanej definicji tych kategorii. Prowadzi to do wielu różnych podejść interpretacyjnych, co szczególnie wyraźnie widać w odniesieniu do demilitaryzacji. Klastycznym przykładem obszaru zmilitaryzowanego i zneutralizowanego są Wyspy Alandzkie. Ze względu na swoje strategiczne położenie kilkukrotnie stały się ważnym elementem politycznych rozgrywek pomiędzy mocarstwami w Europie, na przestrzeni ostatnich dwóch stuleci. Wyspy postrzegano bowiem jako swoisty klucz do realizacji bałtyckiej polityki i równoważenia sił europejskich potęg. Konflikty, które targały regionem w XIX w., doprowadziły do stopniowego wypracowania rozwiązań demilitaryzacji, a później neutralizacji archipelagu, co zostało ostatecznie uregulowane w 1921 r. w międzynarodowej konwencji i potwierdzone po zakończeniu II wojny światowej. Przyjęty wtedy status prawnomiędzynarodowy archipelagu zachował trwałość, a obecnie służy jako swoisty wzorzec efektywnej demilitaryzacji i neutralizacji.
Demilitaryzacja i neutralizacja na przykładzie Wysp Alandzkich
Keywords: demilitarization; demilitaryzacja; neutralization; neutralizacja; Åland Islands; Wyspy Alandzkie; Baltic Sea region; region Morza Bałtyckiego